Combat climate change challenges in considering climatic vulnerabilities and risk factors for wheat production - Rahman, MM; Miah, MG; Saha, SR (SAARC Journal of Agriculture, 2017)
The present study was undertaken for assessing the impacts of climate variability on wheat production as well as the field based suggestions opined by the wheat growers to combat the future challenges particularly climate variability during November 2014 to March 2015. The study was conducted at northwest region at Dinajpur sadar and Kaharul upazilas in Dinajpur of Bangladesh. One hundred sixty wheat farmers were selected by using previously pre-tested interview schedules adopting multistage proportionate systematic random sampling technique. Climatic variability was assessed by analysis of long term data of local meteorological station. Assessment of long term climatic data particularly for wheat growing season revealed that minimum temperature has been increased, while maximum temperature and rainfall were decreased. Farmers opinions on these aspects were almost similar. Farmers opined that both surface and ground water levels have been decreased, resulting agricultural drought. Farmers also opined regarding suitable technology to combat climate change impact on wheat production revealed the use of newly recommended varieties. Finally, the outcome of the results could help researchers as well as government and NGOs to take appropriate climate change adaptation policy thus facilitating farmers in sustaining their livelihoods against changing climate in the near future of Northwest region in Bangladesh. SAARC J. Agri., 14(2): 137-149 (2016)